2020
DOI: 10.1111/nph.16812
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic adjustments in the orchid mycorrhizal fungus Tulasnella calospora during symbiosis with Serapias vomeracea

Abstract:  All orchids rely on mycorrhizal fungi for organic carbon, at least during early development. Orchid seed germination leads in fact to the formation of a protocorm, a heterotrophic postembryonic structure colonized by intracellular fungal coils, thought to be the site for nutrients transfer. The molecular mechanisms underlying mycorrhizal interactions and metabolic changes induced by this peculiar symbiosis in both partners remain mostly unknown.  We studied plant-fungus interactions in the mycorrhizal assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 111 publications
(190 reference statements)
0
20
0
Order By: Relevance
“…Interaction between the two organisms resulted in a dramatic alteration to the metabolites secreted by the fungus, with those metabolites having a high abundance in fungus-only conditions being almost completely replaced with a new set of metabolites. In a metabolomics study with orchid mycorrhizal fungi, Ghirardo et al [ 42 ] similarly found a substantial number of metabolites that were associated with symbiotic tissues but not found in free-living controls, and vice versa. Other studies considering the transcriptomic response of tree hosts to ECM fungi at an early pre-symbiotic time point found a significant enrichment in gene expression associated with alterations to metabolic compound processes in the plant or up-regulation of genes in secretion or general metabolism pathways [ 8 , 31 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between the two organisms resulted in a dramatic alteration to the metabolites secreted by the fungus, with those metabolites having a high abundance in fungus-only conditions being almost completely replaced with a new set of metabolites. In a metabolomics study with orchid mycorrhizal fungi, Ghirardo et al [ 42 ] similarly found a substantial number of metabolites that were associated with symbiotic tissues but not found in free-living controls, and vice versa. Other studies considering the transcriptomic response of tree hosts to ECM fungi at an early pre-symbiotic time point found a significant enrichment in gene expression associated with alterations to metabolic compound processes in the plant or up-regulation of genes in secretion or general metabolism pathways [ 8 , 31 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the last few years have seen an increase in the use of omics approaches to investigate the molecular basis of orchid mycorrhizal symbioses [23,45], information is still patchy mainly due to the complexity of this symbiosis, that involves different developmental stages as well as orchid and fungal symbionts with a range of lifestyles. The absence of Limodorum abortivum genome sequence did not make feasible the alignment of transcript short reads directly to a reference genome, thus putatively leading to an incomplete identification of genes.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic [15][16][17] and proteomic [18][19][20] approaches have revealed the upregulation of several plant membrane transporters in mycorrhizal protocorms, including amino acid transporters and bidirectional sugar transporters of the SWEET (Sugars Will Eventually be Exported Transporters) family [15,21,22]. Interestingly, a recent metabolomic study revealed that the external mycelium of the mycorrhizal fungus Tulasnella calospora growing near the host protocorms showed significant metabolic changes, mainly in lipid metabolism [23].…”
Section: Introductionmentioning
confidence: 99%
“…Plants mainly obtain N nutrition by absorbing and , but organic N is the major source transferred to orchid hosts from fungi ( Cameron et al, 2006 ; Kuga et al, 2014 ; Ghirardo et al, 2020 ). In addition, SvAAPs, SvLHT , and SvOPTs were more abundant in mycorrhizal protocorms ( Fochi et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%